Enhancement of Methylene Blue Adsorption by Acid-Base Neutralization-Induced Bulging MXene/RGO Composite Foams - Jiang, Wenshuai (Langmuir : the ACS journal of surfaces and colloids, 2024)
Nanocomposite films made from graphene oxide (GO) and MXene have a dense layered structure due to nanosheet self-stacking, limiting their dye adsorption performance. In this study, acid-base neutralization reactions are used to induce MXene/reduced graphene oxide (RGO) films bulging, which opens the stacked layer structure within the membrane and enhances MB adsorption performance. The effects of the pH, temperature, contact time, and initial concentration of MB on the adsorption performance are further investigated. The results indicate that the adsorption process conforms to the pseudo-second-order kinetic and Freundlich isotherm models and is heat-absorbing and spontaneous, and the MXene/RGO foams have an adsorption capacity of up to 1099.5 mg g-1 for MB. In addition, our study show that the MXene/RGO foams not only have better reusability, but also exhibit better adsorption for other dyes. The efficient MB removal is attributed to the increased specific surface area of the composite foams, increased active sites, strong electrostatic interactions between MB and the composite foams, as well as intercalation adsorption. These findings offer new options for solving dye effluent problems